The Logic of Social Practices II - Giovagnoli, Raffaela; Lowe, Robert (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book reports on cutting-edge research concerning social practices. Merging perspectives from various disciplines, including philosophy, biology, psychology and cognitive science, and economy, it discusses theoretical aspects of social behavior along with models to investigate them, and presenting key case studies as well. Further, it describes concepts related to habits, routines, and rituals and examines important features of human action, such as intentionality and choice, exploring the influence of specific social practices in different situations. Based on a workshop held on April 2022 at the World Congress on Universal Logic (UNILOG 22), in Crete, and including additional invited chapters, the book offers fresh insights into the fields of social practice and the cognitive, computational, and philosophical tools to understand them.
1. Making Collective Practices into Psychological Facts: the Russian Psychology Model -- 2. Deep Learning Opacity, and the Ethical Accountability of AI Systems. A New Perspective -- 3. The Human Condition at the Crossroads of Biology, Economy, and Ethics -- 4. Inferring Reasons, Internal and External Reasons in Practical Cognition -- 5. Ethical Issues Related to the Predominant Weltbild: The Pythagorean vs. the post-Einstein Age -- 6. Collective Intentionality and the Transformation of Meaning -- 7. During the Contemporary Rituals of Birth -- 8. Habits, Motor Representations and Practical Modes of Presentation -- 9. Russian dacha as a social practice in the crisis times -- 10. About the relationship between ethics and the economy in Aristotle -- 11. Habitual Behavior: Reduction of Complexity of Human Daily Life.
Keywords: Logic; Social sciences -- Philosophy; Cognitive psychology; Logic; Social Philosophy; Cognitive Psychology